1986
DOI: 10.1080/02724936.1986.11748402
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrition and birthweight: selective review and some results of observations in Machakos, Kenya

Abstract: A selective review of maternal nutrition and birthweight is presented. Data from an observational, longitudinal study in Machakos, Kenya show that the habitual diet of pregnant women provided about 1600 kcal and 50 g of protein per day. Nevertheless the birthweight was acceptable, i.e., the mean value was 3058 g. This good reproductive performance was attributed to the fact that weight-for-height remained acceptable during pregnancy, in spite of low weight gain because of an acceptable pre-pregnant weight. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The mothers in Gamboula gained only 5.5 kg in weight during pregnancy while women from affluent societies gain about 12.5 kg (Hytten 1980). A similar result has been reported from other parts of Africa (Bantje 1986;Kusin & Jansen 1986;Möller et al 1989). The low gestational weight gain in developing countries has been taken as an indication of lack of food.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The mothers in Gamboula gained only 5.5 kg in weight during pregnancy while women from affluent societies gain about 12.5 kg (Hytten 1980). A similar result has been reported from other parts of Africa (Bantje 1986;Kusin & Jansen 1986;Möller et al 1989). The low gestational weight gain in developing countries has been taken as an indication of lack of food.…”
Section: Discussionsupporting
confidence: 83%
“…The low gestational weight gain in developing countries has been taken as an indication of lack of food. However, two studies could not find any evidences of constrained food availability (Kusin & Jansen 1986;Thomson et al 1966). As pointed out by Thomson et al (1966), this is also contradicted by the good weight gain of infants that are exclusively breastfed during their first months of life, a period that is more demanding on maternal energy intake than the pregnancy (van Raaij et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…While inadequate pregnancy weight gain is known as a risk factor for LBW (Varma, 1984;Kusin & Jansen, 1986;Aaroson & Machee, 1989) the present data showed that the risk for LBW was only related to mothers' educational level. These findings suggested that less educated women were more likely to be low gainers.…”
Section: Discussionmentioning
confidence: 43%
“…A large number of studies have examined non-nutritional factors in relation to birthweight. It has been established that birthweight is lower among primiparae than among women of higher parity (Kramer 1987;Cnattingius et al 1992); among the very young and among older women (Kramer 1987;Wen et al 1990); among women of low socioeconomic status (Kramer 1987;Gould & LeRoy 1988;Alberman 1994); and among women with slight body build (Averi et al 1982;Kusin & Jansen 1986;Neggers et al 1992;Johnson et al 1994a,b;. Bleeding during pregnancy, particularly during the third semester (Batzofin et al 1984;Strobino & Pantel-Silverman 1989;Ferraz et al 1991), gestational hypertension (Kramer et al 1990), pregnancy toxaemia (Long et al 1980), and a history of miscarriages (Hogue et al 1982;Pickering & Forbes 1985) have been reported as associated with low birthweight, whereas there is limited evidence that induced abortions affect birthweight in subsequent pregnancies (Hogue et al 1982).…”
Section: Introductionmentioning
confidence: 99%